A Cultural Bridge Between Oral Traditions and Health Perspectives in Acehnese Maternal Taboos - Yunisrina Qismullah Yusuf; Diana Fauzia Sari; Ima Indirayani; Azkiya Azkiya (Masyarakat Linguistik Indonesia Universitas Andalas, 2026)
This study examined Acehnese maternal taboos and their relationship with health perspectives through an anthropological and linguistic approach in Banda Aceh and Aceh Besar, Indonesia. It explored how traditional beliefs coexist with modern health knowledge within their cultural contexts. The study contributes theoretically by indicating that maternal taboos represent an evolving knowledge system where cultural meanings, intergenerational transmission, and health interpretations interact rather than exist as separate domains. Data were collected through interviews with 12 women (pregnant women, those with previous pregnancy experience, and caregivers), two obstetricians, and two midwives selected based on their maternal health expertise. Participants were from various areas of Banda Aceh and Aceh Besar, while healthcare professionals had 5–25 years of clinical and academic experience. The findings revealed that Acehnese maternal taboos comprise five categories: dietary, life safety, time, place, and activity. Dietary restrictions were the most prevalent, particularly concerning foods consumed during pregnancy and the postpartum period. Among 34 documented taboos, 22 partly corresponded with health-related considerations, such as avoiding sugar cane due to its high sugar content, reflecting a connection between traditional practices and health knowledge. These health-related maternal taboos reflect three interconnected views of pregnancy: bodily vulnerability, environmental influence, and moral responsibility. These practices regulate food intake, environmental interactions, and maternal behavior, indicating that Acehnese maternal knowledge constructs health through the relationship between the body, surroundings, and social obligations rather than biological mechanisms alone. The remaining 12 emerged primarily from cultural or supernatural beliefs, such as avoiding outdoor activities at sunset to prevent unseen disturbances. Although some practices lack support from current health perspectives, they remain widely observed and transmitted across generations. They emphasize the enduring influence of oral tradition in shaping Acehnese cultural identity and social values.